2021
DOI: 10.1371/journal.pone.0250065
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of tobacco use in Qatar: Prevalence and its associated factors

Abstract: Tobacco use is a serious public health concern as it causes various deleterious health problems. The aim of this study was to determine the prevalence of tobacco use and various types of tobacco used among a population-based sample of adults 18 years and above in Qatar (residents and expatriates). The study also attempted to assess tobacco use initiation age, tobacco dependency, and to identify factors associated with current tobacco use. This 2019 cross-sectional study was conducted among governmental employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
2
19
1
Order By: Relevance
“…Interestingly, our sample showed that cigarette smoking is almost twice as prevalent as WP smoking, which is consistent with a recent study on the Qatari population showing that 21% of tobacco users consumed WP, while 43% smoked cigarettes 36 . Nevertheless, the recent trend of tobacco use decline presents a shift towards WP consumption, particularly from occasional or social use to daily and/or individual use 36 .…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our sample showed that cigarette smoking is almost twice as prevalent as WP smoking, which is consistent with a recent study on the Qatari population showing that 21% of tobacco users consumed WP, while 43% smoked cigarettes 36 . Nevertheless, the recent trend of tobacco use decline presents a shift towards WP consumption, particularly from occasional or social use to daily and/or individual use 36 .…”
Section: Discussionsupporting
confidence: 92%
“…16 While in Qatar, 21.5% of adults are smokers. 17 The relationship between smoking and development of type 2 diabetes (T2DM) is well established. However, the exact mechanism is not fully understood.…”
Section: Reply From the Authormentioning
confidence: 99%
“…Qatar is one of the countries in the region with high smoking rates, currently at 25.2% smoking prevalence among adults. This has led to country -wide efforts to implement strategies to reduce smoking prevalence [ 4 ] that has included nationwide comprehensive policies (e.g., taxation, smoke-free laws) with recent efforts to develop local quitlines to provide individual counseling, given this approach has been highly effective in promoting smoking cessation internationally [ 5 ]. A major component of the effectiveness of the behavioral approaches to smoking behavior change, is the building of client self-efficacy [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%